Amine free direct air capture integrated with buildings’ cooling systems in humid environments - Yasser M. Abdellatif (23072722) (2025)
Direct air capture, among the negative emission technologies, is well positioned to reach climate goals. However, adsorption-based direct air capture system faces significant challenges in humid environments due to water-CO2 co-adsorption, which substantially increases thermal regeneration energy requirements and negatively impacts overall efficiency. To overcome this problem, this study presents novel direct air capture systems integrated with air handling units incorporating a silica gel wheel to dehumidify air before the adsorption process. Dehumidification of air by integrated silica gel wheel enhances the performance of physisorbents and chemisorbents such as NbOFFIVE, Zeolite-13X, SBA-15 functionalized with tetraethylenepentamine, SBA-15 functionalized with L-PEI, and Lewatit by reducing moisture, thereby improving CO2 capture efficiency in humid environments. After capture, saturated part of silica gel wheel meet the moisture-free airstream and regenerate the water without heating and raising the stream humidity approaching the desired indoor humidity levels. The findings presented are supported by both experimental work and mathematical models. This integration significantly reduces thermal regeneration energy requirements by 82 % for NbOFFIVE and 39 % for SBA-15 with tetraethylenepentamine compared to non - silica gel wheel configurations. Moreover, compared to operating direct air capture and heating, ventilation, and air conditioning systems separately, in which their combined thermal energy is 304.73 kWh/day, the integrated system consumes only 128.52 kWh/day of thermal energy, cutting total thermal energy use by 57.8 %. Even against heating, ventilation, and air conditioning system alone (149.08 kWh/day), it achieves a thermal energy saving of 13.8 %. Other Information Published in: Energy Conversion and Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.enconman.2025.120544